Analisis Visual Konten Media Sosial Instagram @Sugerdedi.Id Untuk Membangun Brand Image - Ayunin Nikmah; Ilham Setyawan; Izzaty Zephaniah; Feri Johansah; Deny Febrian; Arrum Dara Efda (Mathematics Education Study Program, 2025)
This study aims to analyze how the visual content on Instagram @sugerdedi.id contributes to the brand image of Sugerdedi Café. This research employs a descriptive qualitative method with visual content analysis based on New Media theory. Data were collected by observing Instagram posts from September to November 2024, focusing on visual elements such as typography, colors, logos, and user interactions (likes, comments, shares, and profile visits). The findings indicate that Sugerdedi Café effectively utilizes visual elements to strengthen its brand identity on Instagram. The use of red, yellow, and brown colors, along with the Montserrat font, establishes a warm and professional brand image. While visual branding remains consistent, audience interaction and follower growth have fluctuated. KPI analysis suggests that engagement rates and reel views have yet to reach optimal levels, requiring more relevant content strategies to enhance interaction and reach. The strategic use of new media and strong aesthetic elements can help Sugerdedi Café reinforce its brand image and attract more customers.